(3GdahGFO GdefJbGI ef JGQjN UGMH MeGgs - (3GHf MHjH GdMdHj , GHf MHjH GdMfaj, HOQ GdOjf CHh eMeO,J (B779 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOGddg eHjO GdCee , bGd (B: (3agPg ChQGb JTJed Ydi PcQ HYV GdCfHjGA Ydjge GdSdGe hLeGYI ef GdNdaGA hGdedhc hGdMcGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B97 - (3U(B149s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJjGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B208 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B206 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B169s
Keywords: (3GdJGQjNs